Pertumbuhan Planlet Nenas (Ananas comosusL. Merr.) Varietas Smooth Cayenne Hasil Kultur In Vitro pada Beberapa Konsentrasi BAP dan Umur Plantlet - Ramadhani Dwi Santoso; . Sobir (Departemen Agronomi dan Hortikultura, 2013)
The aim of this research is to study the effects of synthetic cytokinin (6-benzylaminopurine/BAP) treatments on two groups of pineapple (Ananas comosusL.Merr.) plantlets differentiated by plantlet ages. The research used the Factorial Experiment on Randomized Complete Block Design with two factors, which are BAP concentrations (0 ppm, 25 ppm, 50 ppm, and 75 ppm) and plantlet division by age grouping (52 days and 69 days), with three replications. It was then followed by Tukey’s Honestly Significant Difference Test at error level of 5%. The results show that BAP treatments with the concentration used in this research significantly inhibits the growth of pineapple plantlets observed on four variables (number of leaves, leave length, plantlet height, and plantlet diameter), while age grouping treatments didn’t show any significant effects, except on the plantlet height at 8 and 14 weeks after treatment. There are also treatment-related interactions which significantly affects the number of leaves and plantlet height. It was then suggested that lower concentrations of cytokinin are required if similar research is to be conducted in the future.Keywords : pineapple, post-acclimatization, propagation, 6-benzylaminopurine